Academic Supervision Practices in Strengthening Teacher Professional Competence: Evidence from a Pesantren-Based Madrasah - Fadlillah Fadlillah; Zainullah Zainullah (Yayasan Avicenna, 2022)
Professionalism of teachers is often associated with several important factors, namely teacher competence, teacher certification, and teacher professional allowances. These three factors are believed to be closely related to the advancement or decline of the quality of education in Indonesia. Therefore, the issue of teacher's professional competence needs to receive special attention or serious consideration from the school principal as the teacher's mentor. This research was conducted at madrassa based on pesantren with the aim of analyzing the implementation of academic supervision by the school principal in enhancing teacher's professional competence. The research focuses on implementation of Academic Supervision by the school principal in enhancing teacher's professional competence. This research employs a qualitative approach with a case study design. Data collection techniques include interviews, observations, and documentation. The research subjects are the school principal, vice principal, and teachers. Data analysis involves data reduction, data presentation/display, and drawing conclusions. Data validity is ensured through data triangulation. The research findings show that the implementation of Academic Supervision by the school principal in enhancing teacher's professional competence at madrassa based on pesantren includes individual techniques (observation, classroom visits, individual meetings, direct and indirect approaches) and group techniques (routine meetings, group discussions, and demonstrations, workshops).